Study The poetry of Bashar between influence and being influenced - Mohammed, Mohammed Abdullah; Abdel Rahman, Gamal El Din Ibrahim; Ibrahim, Ibrahim Abdullah (Journal of Humanities & Social Sciences, 2018)
The importance of this subject is reflected in the fact that it deals with the poetry of Bashar between influence and being influenced, because he needed more study and analysis at this time where there are many critical schools. The study dealt with: the poet's relation and his birth, the effect of blindness, his ties with the isolationism,(Mu'tazila) populism, which paved the way to his death by the Caliph Almahdi.This research is considered to be a deep study to the poetry of Bashar, and the extent of its impact , in addition to his being influenced by the surrounding factors. We can discover that the poet has shown his ability in sensory and moral analogy in a way that surpasses the free eyes ownersResearch results:- The impact of blindness in Bashar's mood, and the slavery that his father has experienced are quite visible.- Populism and heresy have deeply influenced Bashar's mood and poetry.- The Abbasid literature was influenced by Bashar's poetry because he was the leader of the none pure Arab poets, but influenced by the Abbasid era, which was distinguished for the power of the Caliphate, the great caliphs, and the glory of the state, influenced by other civilizations.- The poet has benefited from his life in the Badia (rural areas), and also benefited from the lords of speech in his linguistic dictionary.- The poet intertwined the old and the new in his poetry.
Keywords: poetry; influence; vulnerability; Bashar